Participatory Development and Economic Empowerment: Tracing the Socio-Economic Impacts of Village Funds in Eastern Indonesia - Manurung, Juita Ratna Sari; Madubun, Jusuf; Muhtar, Muhtar (Baileo: Jurnal Sosial Humaniora, 2023)
This study aims to analyze the role of Village Fund Allocation (ADD) policies in addressing social disparities in Tawiri Village, Teluk Ambon District, as part of participatory development and economic empowerment efforts in Eastern Indonesia. A qualitative descriptive approach was employed, with data collected through in-depth interviews, field observations, and documentation, utilizing both primary and secondary sources. The study focuses on four key aspects: (1) improving human capital, (2) ensuring equal access for all community members, (3) optimizing the management and utilization of local resources, and (4) promoting equitable development and job creation. The findings reveal that ADD policy in Tawiri has had a positive impact on human resource development and community access to development programs. Village funds are managed effectively, contributing to more equitable infrastructure distribution and the creation of new employment opportunities. The novelty of this study lies in its integrated analysis of the socio-economic impacts of ADD within a local context in Eastern Indonesia—an area often underrepresented in national academic discourse. The study recommends strengthening village institutional capacity and community participation as sustainable strategies for promoting social justice and advancing locally grounded social science knowledge.